2005
DOI: 10.1073/pnas.0505166102
|View full text |Cite
|
Sign up to set email alerts
|

Expression of DNA polymerase β cancer-associated variants in mouse cells results in cellular transformation

Abstract: Thirty percent of the 189 tumors studied to date express DNA polymerase ␤ variants. One of these variants was identified in a prostate carcinoma and is altered from isoleucine to methionine at position 260, within the hydrophobic hinge region of the protein.Another variant was identified in a colon carcinoma and is altered at position 289 from lysine to methionine, within helix N of the protein. We have shown that the types of mutations induced by these cancer-associated variants are different from those induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
147
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 110 publications
(150 citation statements)
references
References 27 publications
2
147
1
Order By: Relevance
“…Variant sequences were confirmed by direct sequencing at the Keck DNA Sequencing Facility, Yale University School of Medicine. For retroviral infection into mouse cells, the wild-type pol ␤ cDNA with a C-terminal hemagglutinin (HA) tag was cloned into the pRVYtet retroviral vector as described previously (23). pol ␤ variant sequences were generated and confirmed using the above protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variant sequences were confirmed by direct sequencing at the Keck DNA Sequencing Facility, Yale University School of Medicine. For retroviral infection into mouse cells, the wild-type pol ␤ cDNA with a C-terminal hemagglutinin (HA) tag was cloned into the pRVYtet retroviral vector as described previously (23). pol ␤ variant sequences were generated and confirmed using the above protocol.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that K289M variant protein induces cellular transformation in immortalized mouse epithelial cells by increasing the mutation frequency of the cells (22,23). We have also shown that this variant is a sequence context-dependent mutator, in that it induces mutations at a frequency 16 times higher than wild-type (WT) pol ␤ within a nucleotide sequence context found in the adenomatous polyposis coli gene that is frequently mutated in colon cancer (22,24).…”
mentioning
confidence: 99%
“…37 Anchorage independent growth was assessed as described previously. 38 After thawing and growing cells until confluence in EGF supplemented media (20 ng/ml), cells were plated into conditions of study for 2 passages. For estrogen depletion experiments phenol red free DMEM/F12 medium (Invitrogen) and 5% charcoal-stripped horse serum (Thermo Fisher), were used, and Tamoxifen or estrogen was added to a final concentration of 1uM after the first passage, as appropriate.…”
Section: Isogenic Cell Line Creationmentioning
confidence: 99%
“…[11][12][13] Specifically, expression of either the K289M colon or I260M prostate cancer Pol β variant in mouse fibroblasts, in the presence of endogenous wild-type Pol β, results in cellular transformation as assessed by focus formation and anchorage independent growth. [11][12][13] A mutagenic basis for the transforming activity of the Pol β variants is suggested by the findings that different clones of cells expressing these polymerases were not immediately transformed but acquired the transformed phenotype after a variable number of passages and that the transformed phenotype persisted even after the expression of the Pol β variant was extinguished. The latter finding indicates that the Pol β variants induce transformation by a "hit-and-run" mechanism in which the continued expression of the initiating event is not required to maintain the transformed state.…”
Section: Pol β β Tumor-associated Variants Are Linked To Cancer Etiologymentioning
confidence: 99%